ChemInform Abstract: Molecular Iodine‐Mediated Chemoselective Synthesis of Multisubstituted Pyridines Through Catabolism and Reconstruction Behavior of Natural Amino Acids. Issue 20 (April 2016) - Xiang, Jia‐Chen; Wang, Miao; Cheng, Yan; Wu, An‐Xin
Abstract: The environmentally benign method offers access to various 2, 6‐ and 3, 5‐disubstituted as well as 2, 4, 6‐trisubstituted pyridines.